Development of Technology for the Production of Masonry Mortars for Masonry Walls of Silicate Brick - Rakhimov Rakhimbai Atazhanovich; Marupova Gulmira; Rakhimov Feruzbek; Sabirova Sabo; Ruzmetova Shohista, (European Journal of Life Safety and Stability (2660-9630), 2022)
This article discusses the possibility of obtaining ultradispersed amorphous silica from rice husks using thermomechanical activation methods. The compositions of the modified masonry mortar were developed and the average value of the coefficient was investigated. adhesion strength and the nature of separation.